Upregulation of Extracellular Vesicles-Encapsulated miR-132 Released From Mesenchymal Stem Cells Attenuates Ischemic Neuronal Injury by Inhibiting Smad2/c-jun Pathway via Acvr2b Suppression - Feng, Bin; Meng, Lei; Luan, Liming; Fang, Zhihao; Zhao, Peng; Zhao, Guangyu (Frontiers in Cell and Developmental Biology, 2021)
Ischemic cerebrovascular disease is a common and frequently-occurring disease among world. The emerging roles of mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) in ischemic neuronal injury have been recently discussed. This study aims to investigate role of EV-derived miR-132 from MSCs in ischemic neuronal injury. EVs were isolated from BMSCs and evaluated. Mouse model of MCAO was constructed and its neurological function were evaluated using neurological scores, pole test and foot fault test. Histopathological changes, neuron viability and apoptosis as well as cerebral infarction were detected by HE staining and TTC staining. The targeting relationship between miR-132 and Acvr2b was verified using dual-luciferase reporter gene assay. Loss- and gain-of-function assays were conducted to determine roles of miR-132, EV-derived miR-132, Acvr2b and Smad2 in oxygen-glucose deprivation (OGD)-treated neurons, and in mice models. Neuronal cell viability and apoptosis were evaluated using CCK-8 and flow cytometry. Acvr2b was highly expressed, while miR-132 was poorly expressed in MCAO mice and OGD-treated neurons. Silencing of Acvr2b or upregulation of miR-132 resulted in increased neuronal activity, decreased neuronal apoptosis, reduced expression of Bax and Cleaved-caspase 3, as well as rising Bcl-2 expression. The expression of Acvr2b was targeted and inhibited by miR-132. EV-derived Acvr2b promoted activation of pSmad2/c-jun signaling pathway, hence inducing neuronal injury. Overexpression of c-jun inhibited protective role of MSCs-derived EV-miR-132 in neuronal injury. Upregulation of EV-derived miR-132 released from MSCs attenuated ischemic neuronal injury by inhibiting Smad2/c-jun pathways via suppression of Acvr2b.